2011
DOI: 10.1111/j.1545-5300.2011.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Preventive Mental Health Interventions for Refugee Families in Resettlement

Abstract: In refugee resettlement, positive psychosocial outcomes for youth and adults depend to a great extent on their families. Yet refugee families find few empirically based services geared toward them. Preventive mental health interventions that aim to stop, lessen, or delay possible negative individual mental health and behavioral sequelae through improving family and community protective resources in resettled refugee families are needed. This paper describes 8 characteristics that preventive mental health inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 45 publications
4
123
0
1
Order By: Relevance
“…The many social services agencies serving Afghans in Alameda County, where we recruited participants for this study, could facilitate this. Weine [34] though suggests that in addition to improving refugee community bonds, building social bridges between refugee and non-refugee communities is necessary for promoting integration, and to avoid having strongly bonded but disconnected communities. In relation to this, previous research has argued that strong ethnic identity (likely found in bonded communities) sometimes increases the negative influence of discrimination [23], because discrimination is perceived as assaulting a core part of the self.…”
Section: Discussionmentioning
confidence: 99%
“…The many social services agencies serving Afghans in Alameda County, where we recruited participants for this study, could facilitate this. Weine [34] though suggests that in addition to improving refugee community bonds, building social bridges between refugee and non-refugee communities is necessary for promoting integration, and to avoid having strongly bonded but disconnected communities. In relation to this, previous research has argued that strong ethnic identity (likely found in bonded communities) sometimes increases the negative influence of discrimination [23], because discrimination is perceived as assaulting a core part of the self.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant remaining buildings are 1970s concrete multistoreys (under ten storeys), indicating there must have been an engineering practice in reinforced concrete introduced during this era that made these buildings more resilient to the movement that causes earthquake damage. While the vast majority of community aid following disaster is based on infrastructure rehabilitation, social networks are also an important aspect of rebuilding and the nurturing of social networks develops trust and interconnectedness [22]. However, it is the social effect of the trauma of earthquake, or constant demolition, or the large rents in the fabric of the built form that has characterised Christchurch's citizen's everyday lives that also demands the most attention.…”
Section: Building and Infrastructure: Modern Examplesmentioning
confidence: 99%
“…These are non-specific distress, health problems or concerns (somatic complaints and medical conditions, quality of sleep), chronic problems in living (interpersonal relationships, occupational stress and financial stress, ecological stress), psychosocial resource loss (perceived social support, social embeddedness, self-efficacy, optimism) and problems specific to youth (clinginess, dependence, loss of sleep, aggressive behaviour, separation anxiety) [32]. As Weine points out, it is only comparatively recently that scholars have integrated 'social capital measures into a quantitative study of rehabilitation' [33]. Social capital is defined as the 'networks, norms and social trust that facilitate coordination and cooperation for mutual benefit' [11].…”
Section: International Development 124mentioning
confidence: 99%
See 2 more Smart Citations